Add 10 to both sides to cancel out the 10
divide 2 on both sides
X= 18
-3x - 18 = 0
-3x = 18
x = -6
Answer:
B
Step-by-step explanation:
I'm positive its B, if it's not B then then D
hope this helps!
You seem to have
.. g(x) = {(2x^2 -4x -16)/(x -4) . . . x ≠ 4
.. .. .. .. ..{ kx -16 . . . . . . . . . . . . . . x=4
The first expression can be simplified to
.. (2x^2 -4x -16)/(x -4) = 2(x +2)(x -4)/(x -4) = 2(x +2) . . . . x ≠ 4
At x=4, this simplified version has the value
.. 2(4 +2) = 12
To make the alternate definition of g(x) have that same value at x=4, we must have
.. k*4 -16 = 12
.. 4k = 28
,, k = 7
The constant k must be 7 for the function to be continuous at x=4.
Use order of operations PEMDAS
Here the parentheses are worked out first .
(27.45-14.61)-[12.53-36.75]
= (12.84) - (-24.22)
= 12.84 + 24.22
= 37.06 Answer